On Continuous Frames in Hilbert $C^*$-Modules - Hadi Ghasemi; Tayebe Lal shateri (Sahand Communications in Mathematical Analysis)
In the present paper, we study continuous frames in Hilbert $C^*$-modules and present some results of these frames. Next, we give the concept of dual continuous frames in Hilbert $C^*$-modules and investigate some properties of them. Also, by introducing the notion of the similarity of the continuous frames, characterizing it, and stating some of its properties, we refer to the investigation of the effect of similarity on the dual continuous frames in Hilbert $C^*$-modules.